2001
DOI: 10.1021/om010753+
|View full text |Cite
|
Sign up to set email alerts
|

New Chromium(III) Complexes as Highly Active Catalysts for Olefin Polymerization

Abstract: Cyclopentadienyl ligands functionalized by quinoline or N,N-dimethylaniline have an ideal and rigid geometry for the formation of half-sandwich compounds. As a result, stable chromium(III) complexes 5−8 with intramolecular nitrogen coordination have been obtained. Treatment with MAO leads to highly active, temperature-stable catalysts for the polymerization of ethylene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
74
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 13 publications
7
74
1
1
Order By: Relevance
“…[19] Higher a-olefins are polymerised as well but with much lower catalytic activity. All compounds need a co-catalyst, which is able to alkylate the metal as well as to abstract an anionic ligand.…”
Section: Polymerisation Resultsmentioning
confidence: 99%
“…[19] Higher a-olefins are polymerised as well but with much lower catalytic activity. All compounds need a co-catalyst, which is able to alkylate the metal as well as to abstract an anionic ligand.…”
Section: Polymerisation Resultsmentioning
confidence: 99%
“…[ 8,12 ] In previous works, the catalytic system used to synthesize disentangled UHMWPE was a bis (phenoxyimine) titanium (IV) dichloride catalyst. [ 8,13,14 ] In order to verify the possibility of achieving such "disentangled" UHMWPE with single-site catalysts not based on group (IV) metals, we have chosen to investigate the suitability of a chromium-based system, namely [1-(8-quinolyl)indenyl] chromium (III) dichloride, reported to synthesize HDPE [ 15 ] when activated with methylaluminoxane (MAO). DFT study performed on a similar catalyst structure [ 7 ] has showed that the main chain termination process is the transfer to the trimethylaluminum (TMA).…”
Section: Introductionmentioning
confidence: 99%
“…[2] Cationic cyclopentadienide chromium(iii) complexes are important examples of such catalysts and display high olefin polymerization activities at room temperature and under 1 atm of ethylene. [3][4][5][6][7][8] As demonstarted by Theopold and co-workers, neutral chromium(iii) complexes that are coordinatively unsaturated and that feature a CrÀ C alkyl s bond are also catalytically active. [9] A series of recent reports demonstrate that cationic olefin-polymerization catalysts can be combined with alkyl aluminum, alkyl magnesium, and alkyl zinc derivatives to afford ethylene oligomers.…”
mentioning
confidence: 99%